STRUCTURAL AND FUNCTINAL FEATURES BLOOD VESSELS AND HEMODYNAMICS TESTICLE IN MEN OF ALL AGES - Nebesna, Z.M.; Gotyur, O.I. (World of Medicine and Biology, 2016)
It is shown the methods of ultrasonic diagnostics, coloured angiography and sciagraphy, that for men by age 22-35 within the limits of seminal rope a testicle artery has in a diameter (1,80±0,15) a mm and artery of seminiferous tubules are (0,80±0,10) a mm, and middle maximal linear to speed of blood. The average maximum speed of blood flow in them rateably (19,5±2,0) cm/s and (13,6 ± 1,0) cm/s rateably. The volume of testicle folds (19,83±1,84) cm3, and diameter of winding seminal tubes - (291,17±1,75) mkm. With age. And especially for men 75-90 these indexes substantially go down : diameter of testcle artery - to (1,2±0,5) the mm, artery of seminiferous tubules - to (0,5±0,1) the mm, middle high speed of arterial blood stream in them - to (14,8±1,0) the cm/s and (9,7±0,2) cm/s, volume of testicle - to (14,50±2,96) cm3, and diameter of winding seminal tubes - to (161,07±6,39) mkm.
Keywords: testicle; blood vessels; haemodynamic